Pengaruh maturity dan secure serta firm size terhadap peringkat obligasi pada perusahaan manufaktur yang terdaftar di bei tahun 2011-2015 - Made Chandra Jaya Saputra; Djoko Setyadi; Musdalifah Aziz (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to determine the effect of maturity, secure and firm size in the bond rating to manufacturing companies listed in Indonesia Stock Exchange and is registered in the rating of bonds issued by PT PEFINDO period 2011 to 2015.In this study the population was 68 manufacturing companies listed in the Indonesia Stock Exchange. The sampling method used is purposive sampling method, in order to obtain 7 companies sampled for 5 years with 140 observation. Data analysis technique used is logistic regression analysis. This research result indicate that firm size and bond secure positive effect on bond ratings. This shows that the firm size and secure can affect the good and bad bond rating companies manufacturing. While the bond maturity has no effect on bond ratings. This means high or low level of bond maturity did not affect the good and bad bond rating companies, especially manufacturing firms in Indonesia Stock Exchange.Keywords: Bond rating, maturity, secure, firm size